Clusters de tecnología para aumentar la competitividad de la ciencia y la tecnología en Ucrania - Hmara, M.P. (Проблеми міжнародних відносин, 2011)
This article analyzes deeply conflictual processes of modern economic internationalization, unprecedented in scale, shock waves of globalization and regional integrationrequire new globally oriented national and regional strategies and models of future development.